Kansas women in agriculture - Varner, Amy (Kansas State University, 2021)
Women have long worked on farms and ranches, although recognition of women involved in agriculture has only become more common in recent years. In the 2017 Census of Agriculture, changes were made to define a producer on a farm. This change allowed for greater recognition of women involved in farming. Kansas saw an increase in female producers involved in agriculture with the change. This study utilizes a survey sent out to women in agriculture who participated in a four-week financial series by K-State Research and Extension. The goal of the survey was to learn more about who these women were, what they wanted to learn, and how they wanted to learn. The results of the study can be used to design programming that will better meet their needs and make them more successful. Survey results were analyzed and summarized to learn more about women in Kansas agriculture. Questions were asked relating to the demographics of the women followed by their employment, work they do on the farm or ranch, what decisions they are involved in on the farm or ranch, and what type of learning experience they are most interested in. Using USDA data for women in Kansas and comparing that information to the survey results gave an idea of the validity of the sample and similarities. Women were able to select the programs that were of the most interest to them. There were 20 options to choose from and women could select as many as programs as they wanted. This information was then compared for the top four categories based on education, compensation, and main occupation. After comparing the top categories tables were created showing the most selected program types based on the main occupation of the respondents whether they were on the farm or ranch or involved in another occupation.
Keywords: Agribusiness; Women; Kansas; Educational programming